Gloss modifier composition and thermoplastic resin composition

A gloss modifier composition of fatty acid zinc salt and ester wax stabilizes gloss suppression and friction in thermoplastic resins, addressing long-term stability and uniformity issues in existing methods.

JP2024177768AInactive Publication Date: 2024-12-24NOF CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023096099
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for suppressing gloss on thermoplastic resin surfaces suffer from variations in gloss over time, lack of long-term stability, and potential interference between gloss modifiers and other surface treatments, leading to uneven surfaces and impaired resin properties.

Method used

A gloss modifier composition comprising a specific fatty acid zinc salt melted into an ester wax, with a defined mass ratio, is added to thermoplastic resins to stabilize gloss suppression and enhance surface friction, ensuring uniformity and long-term stability.

Benefits of technology

The composition effectively maintains low gloss and smooth surface texture over time, improving usability by reducing friction and preventing gloss variations, while maintaining resin properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177768000001
    Figure 2024177768000001
  • Figure 2024177768000002
    Figure 2024177768000002
  • Figure 2024177768000003
    Figure 2024177768000003
Patent Text Reader

Abstract

To provide a gloss modifier composition that imparts low friction to the surface of a thermoplastic resin molded product to improve its usability, while achieving uniform, long-term stable gloss control on the molded product's surface.SOLUTION: A gloss modifier composition for thermoplastic resin comprises a fatty acid zinc salt A melted in an ester wax B. The fatty acid zinc salt A is a zinc salt of an unsaturated fatty acid with 18 to 22 carbons comprising one unsaturated bond in one molecule. The ester wax B is a multifunctional ester compound of a straight-chain saturated fatty acid with 14-24 carbons and at least one polyhydric alcohol selected from pentaerythritol and dipentaerythritol, with a melting point of 60°C or higher. The mass ratio of the fatty acid zinc salt A to the ester wax B is 1:99-30:70.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gloss adjuster composition for imparting low gloss to the surface of a molded article of a thermoplastic resin, and to a thermoplastic resin composition containing the gloss adjuster composition. [Background technology]

[0002] Thermoplastic resin compositions are easily molded and processed, and therefore are used in a wide range of fields, such as electronic devices, automobiles, printing, medicine, furniture, home appliances, and food. It is common to impart required functions to thermoplastic resin compositions in accordance with the required properties for each application, and various functions can be imparted by, for example, surface treatment of molded articles or addition of modifiers to thermoplastic resin compositions.

[0003] For example, in recent years, there has been a trend toward a high-end look in the fields of automobiles, electronic devices, furniture, and home appliances, and there is an increasing demand for parts used in these fields to have a matte, subdued texture with reduced surface gloss. Methods for reducing the gloss of the surface of a molded product generally include a method of providing fine irregularities on the inner surface of a mold during molding, and a method of applying a matting agent to the surface of the molded product. However, these methods have problems such as poor workability or the inherent properties of the resin being impaired.

[0004] Therefore, there is a demand for a material that can be added during molding of a thermoplastic resin to suppress the gloss of the surface of the molded product.For example, Patent Document 1 proposes a method of adding porous spherical resin particles to polycarbonate resin, which is the main component, in order to suppress the gloss of the surface of the molded product.

[0005] In addition, in order to improve the feeling of use of the molded article, it is also required to improve the slipperiness of the molded article surface. For example, a method for improving the slipperiness of the molded article surface can be mentioned, which is a method for reducing the surface friction of the molded article. For example, Patent Document 2 discloses an amide compound capable of reducing the surface friction of a resin molded article. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2022-30130 [Patent Document 2] JP 2016-6122 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, the method disclosed in Patent Document 1 may cause variation in gloss on the surface of the molded article. In addition, since the method disclosed in Patent Document 1 does not fully consider the long-term stability of low gloss, even if a consistent low gloss is obtained, the surface of the molded article may change over time, causing an increase in gloss or variation in gloss. Furthermore, when the amide compound disclosed in Patent Document 2 is used in combination with a gloss regulator for suppressing gloss, the functions of each may be inhibited, and the original effects may not be fully exhibited.

[0008] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a gloss adjuster composition that can impart low friction to the surface of a thermoplastic resin molded article, thereby improving the feeling of use, while at the same time suppressing the gloss of the surface of the molded article stably and without variation over the long term. A further object of the present invention is to provide a thermoplastic composition which is capable of producing a molded article having low gloss, gloss uniformity, and long-term stability thereof, as well as low friction. [Means for solving the problem]

[0009] As a result of intensive research, the inventors have discovered that a composition obtained by dissolving a small amount of a specific fatty acid zinc salt in a specific ester wax serves as a gloss regulator for suppressing gloss while improving the slipperiness of the surface of a thermoplastic resin molded article, and further that a thermoplastic resin molded article to which this composition has been added exhibits low gloss and excellent gloss uniformity over a long period of time, which has led to the completion of the present invention.

[0010] That is, the gloss adjuster composition of the present invention is a gloss adjuster composition for thermoplastic resins, which is obtained by dissolving a fatty acid zinc salt A in an ester wax B, the fatty acid zinc salt A is a zinc salt of an unsaturated fatty acid having 18 to 22 carbon atoms and one unsaturated bond in one molecule, the ester wax B is a polyfunctional ester compound of a linear saturated fatty acid having 14 to 24 carbon atoms and at least one polyhydric alcohol selected from pentaerythritol and dipentaerythritol, and has a melting point of 60° C. or higher; The mass ratio of the fatty acid zinc salt A to the ester wax B (fatty acid zinc salt A:ester wax B) is 1:99 to 30:70.

[0011] The thermoplastic resin composition of the present invention contains the gloss adjuster composition of the present invention and a thermoplastic resin, and is characterized in that the content of the gloss adjuster composition is 0.01 to 10 parts by mass per 100 parts by mass of the thermoplastic resin. Effect of the Invention

[0012] The gloss control composition of the present invention can impart low friction to the surface of a molded thermoplastic resin article, thereby improving the feeling of use, while at the same time suppressing the gloss of the surface of the molded article stably and consistently for a long period of time. In addition, the thermoplastic resin composition of the present invention, which contains the gloss control agent composition of the present invention and a thermoplastic resin, can provide a molded article that has low gloss, gloss uniformity, and long-term stability thereof, as well as low friction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described. In this specification, a numerical range defined using the symbol "~" is intended to include both the upper and lower limits of the symbol "~". For example, "2~10" represents a range of 2 or more and 10 or less.

[0014] Hereinafter, each component contained in the gloss adjuster composition of the present invention, the gloss adjuster composition of the present invention, and the thermoplastic resin composition of the present invention will be described.

[0015] [Fatty acid zinc salt A] The fatty acid zinc salt A contained in the gloss control composition of the present invention is a zinc salt of an unsaturated fatty acid having 18 to 22 carbon atoms and one unsaturated bond in one molecule. The unsaturated bond in the unsaturated fatty acid used in the fatty acid zinc salt A is preferably a carbon-carbon double bond. The unsaturated fatty acid is preferably a straight-chain unsaturated fatty acid, and more preferably a monocarboxylic acid. The unsaturated fatty acid used in the fatty acid zinc salt A may have 18 to 22 carbon atoms, preferably 18 to 20 carbon atoms. Examples of the unsaturated fatty acid used in the fatty acid zinc salt A include oleic acid, elaidic acid, and erucic acid. Specific examples of the fatty acid zinc salt A include zinc oleate, zinc elaidate, and zinc erucate. In the fatty acid zinc salt A, the unsaturated fatty acid may be used alone or in combination of two or more. That is, the fatty acid zinc salt A may be used alone or in combination of two or more. When two or more fatty acid zinc salts A are used in combination, it is preferable to melt-mix the two or more fatty acid zinc salts A before use.

[0016] From the viewpoint of improving the effect of the gloss regulator composition of the present invention in suppressing the gloss of the surface of a molded article stably and uniformly for a long period of time, the fatty acid zinc salt A is preferably at least one selected from zinc oleate and zinc elaidate, more preferably contains at least zinc oleate, and further preferably contains zinc oleate and zinc elaidate in combination. When zinc oleate and zinc elaidate are contained in combination as the fatty acid zinc salt A, the mass ratio of zinc oleate to zinc elaidate (zinc oleate:zinc elaidate) is preferably 99.9:0.1 to 90:10, more preferably 99.9:0.1 to 99:1. When zinc oleate and zinc elaidate are used in combination at a mass ratio of 99.9:0.1 to 99:1, the effect of the gloss regulator composition of the present invention in suppressing the gloss of the surface of a molded article stably and uniformly for a long period of time is further improved.

[0017] Melting point Mp of fatty acid zinc salt A A The temperature is not particularly limited, but from the viewpoint of the fatty acid zinc salt A stably exerting its function for a long period of time and the melting property of the fatty acid zinc salt A in the ester wax B described later, it is preferably 70°C to 100°C, more preferably 75°C to 95°C, and even more preferably 80°C to 85°C. Melting point Mp of fatty acid zinc salt A A is the peak top temperature of the endothermic peak during heating shown in the DSC curve obtained by differential scanning calorimetry (DSC) of fatty acid zinc salt A. The heating rate during DSC heating is 2°C per minute.

[0018] The method for producing the fatty acid zinc salt A is not particularly limited, and examples thereof include a direct method in which a molten fatty acid is directly reacted with a metal oxide or metal hydroxide, and a double decomposition method in which an aqueous solution of a fatty acid alkali metal salt is reacted with an inorganic metal salt.

[0019] [Ester Wax B] The ester wax B contained in the gloss control composition of the present invention is a polyfunctional ester compound of a linear saturated fatty acid having 14 to 24 carbon atoms and at least one polyhydric alcohol selected from pentaerythritol and dipentaerythritol. Examples of linear saturated fatty acids having 14 to 24 carbon atoms include myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, etc. Among them, linear saturated fatty acids having 14 to 22 carbon atoms are preferred, and linear saturated fatty acids having 18 to 22 carbon atoms are more preferred. In the ester wax B, these fatty acids can be used alone or in combination of two or more as the raw fatty acids. The raw material alcohol used in the ester wax B is at least one polyhydric alcohol selected from pentaerythritol and dipentaerythritol. In the ester wax B, as the raw material alcohol, pentaerythritol or dipentaerythritol may be used alone or in combination, but it is preferable to use pentaerythritol or dipentaerythritol alone in terms of ease of controlling crystallinity. As the ester wax B, the polyfunctional ester compounds of the linear saturated fatty acid and the polyhydric alcohol may be used alone or in combination of two or more kinds.

[0020] Melting point Mp of Ester Wax B B The melting point Mp of the ester wax B is 60° C. or higher. This allows the gloss of the surface of the molded article to be stably controlled for a long period of time without variation, and further allows the surface of the molded article to have low friction, improving the feel when used. B The melting point Mp of the ester wax B is preferably 70° C. or higher. B The upper limit of the temperature is not particularly limited, but is usually 100° C. or lower. Melting point Mp of Ester Wax B Bis the peak top temperature of the endothermic peak during heating shown in the DSC curve obtained by differential scanning calorimetry (DSC) of ester wax B. The heating rate during DSC heating is 2°C per minute.

[0021] In order for the gloss control agent composition of the present invention to fully exert the effect of suppressing the gloss of the surface of a molded article stably for a long period of time without variation and the effect of imparting low friction to the surface of a molded article to improve the feel when used, the acid value of the ester wax B is preferably 5 mgKOH / g or less, more preferably 3 mgKOH / g or less, and even more preferably 1 mgKOH / g or less. From the same viewpoint, the hydroxyl value of the ester wax B is preferably 20 mgKOH / g or less, more preferably 10 mgKOH / g or less, and further preferably 5 mgKOH / g or less. The acid value can be measured in accordance with JOCS (Japan Oil Chemists' Society) 2.3.1-1996, and the hydroxyl value can be measured in accordance with JOCS (Japan Oil Chemists' Society) 2.3.6.2-1996.

[0022] The method for producing the ester wax B is not particularly limited, but examples thereof include a synthesis method by oxidation reaction, synthesis from fatty acids or their derivatives, a method using a dehydration condensation reaction between alcohol and fatty acid, a method using a reaction between an acid halide and alcohol, and a method using an ester exchange reaction. A catalyst may be used during the reaction. Examples of the catalyst include general acidic or alkaline catalysts used in esterification reactions, such as zinc acetate and titanium compounds. The ester wax B is obtained, for example, by an esterification reaction using the above-mentioned alcohol or its derivative and the above-mentioned fatty acid or its derivative as raw materials, and is typically obtained by a dehydration condensation reaction between the above-mentioned alcohol and fatty acid. When obtaining the ester wax B, it is preferable to react the raw material alcohol with the raw material fatty acid so that the molar ratio of the hydroxyl groups (-OH) of the raw material alcohol to the carboxyl groups (-COOH) of the raw material fatty acid is 1:1, or so that the amount of the carboxyl groups is slightly greater than the amount of the hydroxyl groups. This makes it possible to easily obtain a polyfunctional ester having an acid value and a hydroxyl value within the above-mentioned preferred ranges. After the esterification reaction, a deacidification step using an alkaline aqueous solution may be appropriately carried out, and the product may be further purified by a recrystallization method, a distillation method, a solvent extraction method or the like.

[0023] [Gloss adjuster composition C] The gloss regulator composition C of the present invention is a composition obtained by melting a fatty acid zinc salt A in an ester wax B. The gloss regulator composition C of the present invention is obtained by melt-mixing a fatty acid zinc salt A in an ester wax B. As a method of melt-mixing, it is preferable to completely melt and mix the fatty acid zinc salt A and the ester wax B at or above their respective melting points. By melting the fatty acid zinc salt A in the ester wax B, in a thermoplastic resin composition containing the gloss regulator composition C of the present invention in a thermoplastic resin, the gloss regulator composition C of the present invention can be bled onto the surface of a molded article of the thermoplastic resin composition as a composition without variation. Therefore, the gloss regulator composition C of the present invention can exert an effect of suppressing the gloss of the surface of a molded article of a thermoplastic resin without variation. In addition, in the case of a molded article of a thermoplastic resin, it is required to improve the slipperiness of the surface in order to improve the feeling of use. By bleeding the gloss control composition C of the present invention onto the surface of a molded article of a thermoplastic resin composition, low friction is imparted to the surface of the molded article, resulting in good slipperiness of the surface and a good feeling of use.

[0024] The mass ratio of fatty acid zinc salt A and ester wax B (fatty acid zinc salt A: ester wax B) contained in the gloss regulator composition C of the present invention is 1:99 to 30:70, preferably 1:99 to 20:80. According to the gloss regulator composition C of the present invention, the ester wax B suppresses the gloss of the surface of the molded article and imparts low friction, and further, by containing an appropriate amount of fatty acid zinc salt A, the effect of suppressing the gloss stably for a long time without variation is further improved. This is considered to be because the crystallinity of the ester wax B is appropriately reduced by the fatty acid zinc salt A, and excessive crystal formation of the ester wax B on the surface of the molded article is suppressed. On the other hand, since the ratio of the fatty acid zinc salt A is a specific amount or less, the effect of the gloss regulator composition C of the present invention is excellent in long-term stability. This is considered to be because the fatty acid zinc salt A is not excessive, and therefore the change over time in the crystal state of the gloss regulator composition C is suppressed. In the gloss regulator composition C of the present invention, the mass ratio of the fatty acid zinc salt A to the ester wax B is more preferably in the range of 3:97 to 15:85, and further preferably in the range of 4:96 to 10:90. In this case, the effect of the gloss regulator composition C of stably suppressing the gloss of the surface of a molded article for a long period of time without variation, and the effect of imparting low friction to improve the feeling of use are further improved.

[0025] The gloss regulator composition C of the present invention can be prepared by melt-mixing one or more fatty acid zinc salts A and one or more ester waxes B. The gloss regulator composition C may contain other components such as impurities contained in the fatty acid zinc salt A or the ester wax B, but the total content of the fatty acid zinc salt A and the ester wax B is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more, based on 100% by mass of the total solid content contained in the gloss regulator composition C of the present invention. The lower the content of impurities, the more excellent the effect of the gloss regulator composition C of the present invention of stably suppressing the gloss of the surface of a molded article without variation for a long period of time, and the effect of imparting low friction to improve the feeling of use.

[0026] The DSC curve obtained by differential scanning calorimetry (DSC) of the gloss control composition C of the present invention shows a single maximum point P C It is preferred that In the DSC curve of gloss adjuster composition C, the maximum point P C is due to the heat generated during the crystallization of the gloss control composition C. That is, the maximum point P C is the peak top of the exothermic peak due to the crystallization of the gloss control composition C. Therefore, the maximum point P C When there is only one of the above points, the gloss modifier composition C has excellent uniformity of crystallization. The less the variation in crystallization of the gloss modifier composition C, the more uniform the composition of the gloss modifier composition C that bleeds onto the surface of the molded article is, and therefore the matte finish, gloss uniformity, and long-term stability thereof of the surface of the molded article provided by the gloss modifier composition C are further improved.

[0027] The maximum point P of the DSC curve during cooling C The number of points is an index of uniform mixing when obtaining a molten mixed product, and the number of points is an index of uniform mixing when obtaining a molten mixed product. C In order to achieve this, it is effective to appropriately select the fatty acid zinc salt A and the ester wax B, and further to appropriately adjust the content ratio of the fatty acid zinc salt A and the ester wax B. For example, it is preferable that the ester wax B used in the gloss regulator composition C is a polyfunctional ester compound of at least one straight-chain saturated fatty acid selected from the group consisting of myristic acid, palmitic acid, stearic acid, arachidic acid, and behenic acid, and either pentaerythritol or dipentaerythritol, and that the fatty acid zinc salt A used in combination with this is at least one selected from zinc oleate and zinc elaidate. The mass ratio of the fatty acid zinc salt A to the ester wax B (fatty acid zinc salt A:ester wax B) is preferably adjusted within the range of, for example, 1:99 to 20:80. The DSC curve of gloss control agent composition C has a single maximum point P CIn order to satisfy the above condition, it is particularly effective to use only one of pentaerythritol and dipentaerythritol as the raw material alcohol for the ester wax B.

[0028] The maximum point Pc during cooling in the DSC curve of the gloss regulator composition C of the present invention can be confirmed by carrying out the following operations using a differential scanning calorimeter (for example, DSC7000X, manufactured by Hitachi High-Tech Science Corporation). First, 10 mg of the measurement sample (gloss regulator composition C) is weighed into an aluminum sample pan. In a measurement folder into which nitrogen is blown at a flow rate of 60 ml per minute, the weighed measurement sample is heated to 200°C at a heating rate of 2°C per minute, and then held at 200°C for 1 minute to make the thermal history between the measurement samples uniform. Thereafter, the measurement sample is cooled from 200°C to 30°C at a heating rate of 2°C per minute to obtain a DSC curve during cooling of the measurement sample. During the cooling, an exothermic peak is confirmed. In the exothermic peak in this DSC curve, the inflection point of the DDSC (DSC differential value) curve, i.e., the point where the DDSC value becomes 0, is referred to as the maximum point Pc described above. C The measurement results can be analyzed using, for example, standard analysis software that comes with the device. When using a DSC7000 manufactured by Hitachi High-Tech Science Corporation as the differential scanning calorimeter, the analysis software that comes with the DSC7000 can be used. In the gloss control composition C of the present invention, as described above, the maximum point P C In other words, it is preferable that the DSC curve shows one exothermic peak during cooling, and that the DSC curve has only one inflection point at the exothermic peak where the inflection point becomes 0.

[0029] In the DSC curve obtained by differential scanning calorimetry of the gloss control composition C of the present invention, the maximum point P C The half-width of the peak with the peak top at ΔT PCThe temperature is preferably in the range of 3° C. to 11° C., and more preferably in the range of 4° C. to 8° C. This further suppresses variation in gloss on the surface of a molded article of a thermoplastic resin by the gloss control agent composition C of the present invention.

[0030] In addition, the dynamic friction coefficient μ C is preferably 0.4 or less, more preferably 0.3 or less, whereby the gloss modifier composition C of the present invention improves the low friction property of the surface of a molded thermoplastic resin article, and as a result, the feel of the molded article when in use is further improved. The above-mentioned dynamic friction coefficient μ C The measurement method is as follows: The gloss modifier composition C was melt-molded into a measurement sample in the form of a plate with a diameter of 5 cm and a thickness of 1 cm, and the dynamic friction coefficient was measured using a Bowden tester with a contact (semi-cylindrical, stainless steel, diameter 1 cm) under the conditions of a load of 100 g, a speed of 2.5 mm / s, a measurement distance of 10 mm, and 10 test runs. The average of the 10 measured values ​​was taken as the dynamic friction coefficient μ of the gloss modifier composition C. C Let us assume that.

[0031] [Thermoplastic resin composition] The thermoplastic resin composition of the present invention contains the above-mentioned gloss regulator composition C of the present invention and a thermoplastic resin D, and the content of the gloss regulator composition C of the present invention is in the range of 0.01 to 10 parts by mass relative to 100 parts by mass of the thermoplastic resin D. A molded article of the thermoplastic resin composition of the present invention in which the content of the gloss regulator composition C of the present invention is within the above range has excellent low surface gloss, gloss uniformity, and long-term stability thereof, and further has a good surface slip and a good feel when used. The content of the gloss regulator composition C is preferably in the range of 0.1 to 5 parts by mass.

[0032] The thermoplastic resin composition of the present invention further improves the low gloss, uniform gloss, and long-term stability of the molded article surface, and further improves the slipperiness of the molded article surface by containing an amorphous thermoplastic resin as the thermoplastic resin D. Examples of the amorphous thermoplastic resin include polystyrene resin, polymethyl methacrylate resin, vinyl chloride resin, acrylonitrile-butadiene-styrene copolymer resin, polycarbonate resin, polyacetal resin, amorphous polyester resin, and styrene-acrylic acid ester copolymer resin.

[0033] The thermoplastic resin composition of the present invention may contain various additives that are generally added to adjust physical properties, as necessary, within the scope of the present invention, such as plasticizers, crosslinking agents, softeners, tackifiers, antistatic agents, fillers, antioxidants, silane coupling agents, zinc oxide, vulcanization accelerators, vulcanizing agents, workability improvers, solvents, etc.

[0034] The thermoplastic resin composition of the present invention can be produced by kneading the gloss control composition of the present invention described above, a thermoplastic resin, and additives added as necessary, by a known method. EXAMPLES

[0035] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples and comparative examples. The measurements for the fatty acid zinc salt A, the ester wax B, and the gloss adjuster composition C were carried out by the following methods. (1) Melting point: 10 mg of a measurement sample was weighed into an aluminum sample pan, and a differential scanning calorimeter (Hitachi High-Tech Science, DSC7000X) was used to measure the melting point. The measured sample was heated from 30°C to 200°C at a heating rate of 2°C per minute in a measurement folder into which nitrogen was blown at a flow rate of 60 ml per minute, and then held at 200°C for 1 minute. The sample was then cooled from 200°C to 30°C at a heating rate of 2°C per minute to make the thermal history between the samples uniform. Then, a DSC curve was obtained when the sample was heated from 30°C to 200°C at a heating rate of 2°C per minute. The melting point was determined as the peak top temperature of the endothermic peak during heating of the obtained DSC curve. (2) Acid value: Measured in accordance with JOCS (Japan Oil Chemists' Society) 2.3.1-1996. (3) Hydroxyl value: Measured in accordance with JOCS (Japan Oil Chemists' Society) 2.3.6.2-1996. (4) Maximum point P C Number of: 10 mg of the measurement sample was weighed out into an aluminum sample pan, and using a differential scanning calorimeter (DSC7000X, Hitachi High-Tech Science Corporation) in a measurement folder into which nitrogen was blown at a flow rate of 60 ml per minute, the weighed measurement sample was heated to 200°C at a heating rate of 2°C per minute, and then held at 200°C for 1 minute to make the thermal history between the measurement samples uniform. The measurement sample was then cooled from 200°C to 30°C at a heating rate of 2°C per minute to obtain a DSC curve of the measurement sample during cooling. The number of points at which the inflection point of the DDSC curve was 0 was identified in the heat generation peak during cooling of the obtained DSC curve, and the maximum point P C The number of pieces was set to . (5) Half-width ΔT PC : Above "(4) Maximum point P C When the measurement result of "Number of pieces" is 1, the maximum point P C The half-width of the peak with the peak top at is ΔT PC It was decided. (6) Dynamic friction coefficient: For a plate-shaped measurement sample with a diameter of 5 cm and a thickness of 1 cm, the dynamic friction coefficient was measured using a Bowden testing machine with a contact (semi-cylindrical, stainless steel, diameter 1 cm) under the conditions of a load of 100 g, a speed of 2.5 mm / s, a measurement distance of 10 mm, and 10 test runs. The average of the 10 measured values ​​was regarded as the dynamic friction coefficient of the measurement sample.

[0036] [Synthesis or preparation of fatty acid zinc salt A] Fatty acid zinc salts A-1 to A-3 were synthesized or prepared as follows. In addition, oleic acid refers to a monounsaturated fatty acid having 18 carbon atoms, in which the 9th position is cis-type, and elaidic acid refers to a monounsaturated fatty acid having 9th position in the trans-type. Table 1 shows the raw fatty acids and melting points Mp A Shows.

[0037] Hereinafter, the amount of substance of compounds with a purity of less than 100% is calculated including impurities. [Synthesis of fatty acid zinc salt A-1 (zinc oleate)] 200g (0.7mol) of oleic acid (Tokyo Chemical Industry Co., Ltd., purity over 99.0%) was placed in a 300mL four-neck flask equipped with a thermometer and a nitrogen inlet tube, and zinc oxide (28.5g, 0.35mol) and water (0.1g) were added dropwise while the liquid in the flask was kept at 90°C. After that, the reaction was carried out at 110°C for 3 hours, and zinc oleate (219.9g, 0.35mol) was obtained by removing the water.

[0038] [Synthesis of fatty acid zinc salt A-2 (zinc elaidate)] Zinc elaidate (219.9 g, 0.35 mol) was obtained in the same manner as in the synthesis of fatty acid zinc salt A-1, except that 200 g (0.7 mol) of elaidic acid (manufactured by Tokyo Chemical Industry Co., Ltd., purity exceeding 97.0%) was used instead of oleic acid.

[0039] [Preparation of fatty acid zinc salt A-3 (zinc stearate)] As the fatty acid zinc salt A-3 (zinc stearate), "Zinc Stearate G" manufactured by NOF Corporation was used.

[0040] [Table 1]

[0041] [Synthesis or preparation of ester wax B] Ester waxes B-1 to B-4 were synthesized or prepared as follows. Table 2 shows the raw material fatty acid, raw material alcohol, melting point Mp of each ester wax B. B , acid value, and hydroxyl value.

[0042] [Synthesis of Ester Wax B-1 (Pentaerythritol Tetrastearate)] 250.0g (1.8mol) of pentaerythritol and 2107.6g (7.4mol) of stearic acid (manufactured by NOF Corp., purity over 98.0%) were placed in a 3L four-neck flask equipped with a thermometer, a nitrogen inlet tube, a stirring blade and a cooling tube, and reacted at 240°C under a nitrogen stream to obtain an ester crude product. The obtained ester crude product had an acid value of 5.7mgKOH / g. 750g of toluene and 200g of 2-propanol were added to this ester crude product, and further, a 10% by mass potassium hydroxide aqueous solution containing potassium hydroxide in an amount equivalent to twice the residual acid value of the ester crude product was added, and the mixture was stirred at 70°C for 30 minutes. After that, the mixture was left to stand for 30 minutes, and the aqueous layer (lower layer) was separated and removed to obtain an ester layer. The obtained ester layer was repeatedly washed with water four times until the pH of the wastewater became neutral. The solvent remaining in the ester layer was distilled off at 180° C. and reduced pressure of 1 kPa, and then filtration was carried out to obtain pentaerythritol tetrastearate (2103.5 g, 1.7 mol).

[0043] [Preparation of Ester Wax B-2 (Pentaerythritol Tetrastearate)] As the ester wax B-2 (pentaerythritol tetrastearate), "Unistar H-476" manufactured by NOF Corporation was used.

[0044] [Synthesis of Ester Wax B-3 (Pentaerythritol Tetrabehenate)] Pentaerythritol tetrabehenate (2424.8 g, 1.7 mol) was obtained in the same manner as in the synthesis of Ester Wax B-1, except that behenic acid (manufactured by NOF Corp., purity over 88%) (2517.5 g, 7.4 mol) was used instead of stearic acid.

[0045] [Synthesis of Ester Wax B-4 (Dipentaerythritol Hexamyristate)] Dipentaerythritol hexamyristate (2578.4 g, 1.7 mol) was obtained in the same manner as in the synthesis of ester wax B-1, except that myristic acid (manufactured by NOF Corp., purity over 98%) (2466.4 g, 10.8 mol) was used instead of stearic acid, and dipentaerythritol (457.7 g, 1.8 mol) was used instead of pentaerythritol.

[0046] [Table 2]

[0047] [Preparation of gloss adjuster composition C] The fatty acid zinc salt A and ester wax B shown in Table 3 were placed in a 0.3 L separable flask equipped with a stirring blade and a nitrogen inlet tube in the mass ratio shown in Table 3, and melt-mixed by stirring under a nitrogen stream at 150°C for 1 hour. After that, the mixture was cooled, solidified, and pulverized to obtain gloss adjuster compositions C-1 to C-14. In the preparation of gloss regulator composition C-1, fatty acid zinc salt A was prepared by melt mixing fatty acid zinc salt A-1 (zinc oleate) and fatty acid zinc salt A-2 (zinc elaidate) in a mass ratio of 99.5:0.5. The melting point Mp of fatty acid zinc salt A used in gloss regulator composition C-1 was A was 82°C. In preparing gloss regulator composition C-9, fatty acid zinc salt A was prepared by melt mixing fatty acid zinc salt A-1 (zinc oleate) and fatty acid zinc salt A-2 (zinc elaidate) in a mass ratio of 90:10. The melting point Mp of fatty acid zinc salt A used in gloss regulator composition C-9 was A was 84°C. In preparing the gloss regulator composition C-10, the ester wax B was prepared by melt-mixing the ester wax B-2 (pentaerythritol tetrastearate) and the ester wax B-3 (pentaerythritol tetrabehenate) in a mass ratio of 20:80. The ester wax B used in the gloss regulator composition C-10 had a melting point Mp B The temperature was 78°C, the acid value was 0.7 mg KOH / g, and the hydroxyl value was 6.7 mg KOH / g.

[0048] Table 3 shows the results of the gloss control compositions C-1 to C-14, including the fatty acid zinc salt A and ester wax B as raw materials, and the maximum point P c The number of maximum points P c The half-width of the peak with the peak top at ΔT PC , and the dynamic friction coefficient μ C Shows. In addition, in all of the obtained gloss adjuster compositions C-1 to C-14, the total content of fatty acid zinc salt A and ester wax B relative to the total solid content in gloss adjuster composition C (100% by mass) was 98% by mass or more.

[0049] [Table 3]

[0050] As shown in Table 3, gloss adjuster compositions C-1 to C-10 were gloss adjuster compositions of the present invention in which the above-mentioned fatty acid zinc salt A was dissolved in ester wax B, and the mass ratio of fatty acid zinc salt A to ester wax B was within the range of 1:99 to 30:70. On the other hand, gloss regulator compositions C-11 to C-14 did not correspond to the gloss regulator compositions of the present invention. Gloss regulator composition C-11 did not contain ester wax B, and consisted of fatty acid zinc salt A. Gloss regulator composition C-12 did not contain fatty acid zinc salt A, and consisted of ester wax B. Gloss regulator composition C-13 had a mass ratio of fatty acid zinc salt A to ester wax B of 40:60, and the proportion of fatty acid zinc salt A was high. Gloss regulator composition C-14 had a fatty acid zinc salt A as a raw material fatty acid, which was a saturated fatty acid.

[0051] [Preparation of Thermoplastic Resin Composition] (Examples 1 to 13, Comparative Examples 1 to 7) The types and amounts of gloss control agent composition C and thermoplastic resin D shown in Table 4 were melt-kneaded at 260°C in a twin-screw kneader, cooled, and then pulverized to prepare the thermoplastic resin compositions of Examples 1 to 13 and Comparative Examples 1 to 7. As the thermoplastic resin D, thermoplastic resin D-1 (polycarbonate resin, manufactured by Mitsubishi Engineering Plastics Corporation, "Iupilon S1000") was used. In addition, in Comparative Example 5, gloss adjuster composition C-11 (only fatty acid zinc salt A-1) and gloss adjuster composition C-12 (only ester wax B-1) were used by adding them in the mass ratio shown in Table 4 without being melt-mixed in advance.

[0052] (Examples 14 to 15, Comparative Example 8) The types and amounts of gloss adjuster composition C and thermoplastic resin D shown in Table 4 were melt-kneaded at 130°C, cooled, and then pulverized to prepare the thermoplastic resin compositions of Examples 14 to 15 and Comparative Example 8. As the thermoplastic resin D, thermoplastic resin D-2 (amorphous polyester resin, manufactured by Mitsubishi Rayon Co., Ltd., "Diaclone ER508") was used.

[0053] 〔evaluation〕 The following evaluation tests were carried out using the thermoplastic resin compositions obtained in Examples 1 to 15 and Comparative Examples 1 to 8. The evaluation results are shown in Table 4.

[0054] (Low friction) The thermoplastic resin composition was molded into cylindrical pellets with a diameter of 5 cm and a thickness of 5 mm using a tablet molding machine (product name: benchtop hydraulic molding machine MP250, manufactured by Marsen). The bottom surface of the pellet was heated for 1 second on a hot plate set at the same temperature as the kneading temperature (260°C or 130°C), and then quenched at room temperature. The dynamic friction coefficient of the heated surface of the pellet was measured using a Bowden tester using a contact (semi-cylindrical, stainless steel, diameter 1 cm) under the conditions of load: 100 g, speed: 2.5 mm / s, measurement distance: 10 mm, and number of tests: 10 times, and the average value of the 10 measured values ​​was taken as the dynamic friction coefficient μ of the thermoplastic resin composition. D It was decided. The dynamic friction coefficient of the thermoplastic resin D to which the gloss control composition C was not added was similarly determined, and the dynamic friction coefficient μ DBlank It was decided. Dynamic friction coefficient μ D and the coefficient of dynamic friction μ DBlank Using the above, the reduction rate of the dynamic friction coefficient Kμ is calculated using the following formula (1). D was calculated. Kμ D =μ D / μ DBlank Formula (1) Reduction rate of dynamic friction coefficient Kμ D The larger Kμ is, the more excellent the effect of imparting low friction by the gloss control composition C. D The low friction was evaluated based on the value of . The evaluation criteria are as follows: ◎:Kμ D <0.80 ○: 0.80≦Kμ D <0.90 ×:0.90≦Kμ D

[0055] (Low gloss) A cylindrical pellet similar to the one used for the evaluation of low friction was prepared as a measurement sample. Ten measurement areas on the sample surface were measured using a Gloss Checker IG-320 manufactured by Horiba, Ltd. at an incident angle of 60°C, and the average value was determined as the gloss value G of the thermoplastic resin composition. D It was decided. The gloss value of the thermoplastic resin D to which the gloss control agent composition C was not added was also determined in the same manner. DBlank It was decided. Gloss value G D and gloss value G DBlank Using the above formula (2), the gloss reduction rate KG D was calculated. KG D =G D / G DBlank Formula (2) Gloss reduction rate KG D The larger the value, the better the gloss suppressing effect (low gloss) of the gloss control agent composition C. D The low gloss was evaluated based on the value of 0.01 to 0.01. The evaluation criteria are as follows: ◎:KG D <0.85 ○: 0.85≦KG D <0.95 ×:0.95≦KG D

[0056] (Long-term stability of low gloss) Cylindrical pellets similar to those used in the evaluation of low friction were prepared and stored at 55°C and 85% humidity for one month to carry out an accelerated test. The pellets after the accelerated test were washed with water and dried at room temperature for one day to prepare samples after the accelerated test. The gloss value of the sample after the accelerated test was determined in the same manner as in the evaluation of low gloss described above, and the gloss value G of the thermoplastic resin composition after the accelerated test was calculated. D This gloss value G D ' and the gloss value G of thermoplastic resin D obtained by the above-mentioned evaluation of low gloss. DBlank Using the above formula (3), the gloss reduction rate KG after the accelerated test is calculated. D ' was calculated. KG D '=G D ' / G DBlank Formula (3) In addition, the reduction rate of gloss value after accelerated testing KG D ' and the reduction rate of gloss value KG obtained by the above-mentioned evaluation of low gloss D Using the above, the rate of change CG is calculated using the following formula (4).D was calculated. CG D (%)={|KG D '-KG D | / KG D}×100 Formula (4) Rate of change CG D The smaller the value, the more excellent the long-term stability of the gloss suppressing effect (low gloss) of the gloss control agent composition C. D The long-term stability of low gloss was evaluated based on the value of . The evaluation criteria are as follows: ◎:CG D <3.0 ○:3.0≦CG D <5.0 ×:5.0≦CG D

[0057] (Gloss uniformity) The largest gloss value G among the 10 measurement results of the measurement sample in the low gloss evaluation described above MAX and the smallest gloss value G MIN Using these values, the difference in gloss value ΔG was calculated using the following formula (5). ΔG=G MAX -G MIN Formula (5) The smaller the difference ΔG in gloss value, the smaller the variation in the gloss suppressing effect of the gloss control agent composition C, and the more excellent the gloss uniformity. The gloss uniformity was evaluated based on the ΔG value. The evaluation criteria are as follows. ◎:ΔG<0.5 ○: 0.5≦ΔG<1.0 ×:1.0≦ΔG

[0058] (Long-term stability of gloss uniformity) The largest gloss value G among the 10 measurement results of the sample after the accelerated test for the long-term stability of low gloss mentioned above was MAX ' and the smallest gloss value G MIN Using these values, the difference in gloss value ΔG' after the accelerated test was calculated using the following formula (6). ΔG'=G MAX '-G MIN ' Formula (6) The smaller the difference ΔG' in gloss values ​​after the accelerated test, the smaller the variation in the gloss suppressing effect of the gloss control composition C even after a long period of time, and the better the gloss uniformity. Based on the value of ΔG', the long-term stability of gloss uniformity was evaluated. The evaluation criteria are as follows. ◎: ΔG'<0.5 ○: 0.5≦ΔG'<1.0 ×:1.0≦ΔG'

[0059] [Table 4]

[0060] As shown in Table 4, the thermoplastic resin compositions of Examples 1 to 15, which contain 0.01 to 10 parts by mass of gloss adjuster compositions C-1 to C-10 of the present invention per 100 parts by mass of thermoplastic resin, have excellent low friction, low gloss, and gloss uniformity on the surface of molded articles, whether they use a single component or multiple components as fatty acid zinc salt A or ester wax B, and even after an accelerated test in which the thermoplastic resin composition is stored under high temperature and high humidity conditions, the low gloss and gloss uniformity are maintained, resulting in excellent long-term stability. On the other hand, in the thermoplastic resin compositions of Comparative Examples 1 and 2, the content of the gloss control composition C-1 was less than 0.01 parts by mass or more than 10 parts by mass relative to 100 parts by mass of the thermoplastic resin, and as a result, the low friction, low gloss, and gloss uniformity were all inferior. In the thermoplastic resin composition of Comparative Example 3, the gloss adjuster composition C-11 used was composed only of fatty acid zinc salt A. As a result, the low friction, low gloss, and gloss uniformity were all inferior. In the thermoplastic resin compositions of Comparative Examples 4 and 8, the gloss adjuster composition C-12 used was composed only of the ester wax B. As a result, although the low friction property was good, the low gloss property and the gloss uniformity were poor. To the thermoplastic resin composition of Comparative Example 5, gloss adjuster composition C-11 (only fatty acid zinc salt A) and gloss adjuster composition C-12 (only ester wax B) were added without melt mixing. As a result, although the low friction property was good, the low gloss property and gloss uniformity were poor. The thermoplastic resin composition of Comparative Example 6 used a gloss adjuster composition C-13 containing fatty acid zinc salt A and ester wax B in a mass ratio of 40:60, with a high proportion of fatty acid zinc salt A. As a result, although the low friction, low gloss and gloss uniformity were good, the long-term stability of the low gloss and gloss uniformity was poor. The thermoplastic resin composition of Comparative Example 7 used a gloss adjuster composition C-14 containing a zinc salt of a saturated fatty acid as the fatty acid zinc salt A. As a result, although the low friction property was good, the low gloss property and the gloss uniformity were poor.

Claims

1. A gloss control composition for a thermoplastic resin, comprising a fatty acid zinc salt A dissolved in an ester wax B, the fatty acid zinc salt A is a zinc salt of an unsaturated fatty acid having 18 to 22 carbon atoms and one unsaturated bond in one molecule, the ester wax B is a polyfunctional ester compound of a linear saturated fatty acid having 14 to 24 carbon atoms and at least one polyhydric alcohol selected from pentaerythritol and dipentaerythritol, and has a melting point of 60° C. or higher; A gloss adjuster composition, in which the mass ratio of the fatty acid zinc salt A to the ester wax B (fatty acid zinc salt A:ester wax B) is 1:99 to 30:

70.

2. A gloss control composition comprising the gloss control composition according to claim 1 and a thermoplastic resin, The thermoplastic resin composition has a content of the gloss control agent composition of 0.01 to 10 parts by mass relative to 100 parts by mass of the thermoplastic resin.

Citation Information

Patent Citations

  • Applications as slip and / or antiblocking agent or mold release agent, and polymer mixture

    JP2016006122A

  • Polycarbonate resin composition

    JP2022030130A